Using Multimodal Representations to Support Learning in the Science Classroom - Hand, Brian; McDermott, Mark; Prain, Vaughan (Springer International Publishing : Imprint: Springer, 2016)
This book provides an international perspective of current work aimed at both clarifying the theoretical foundations for the use of multimodal representations as a part of effective science education pedagogy and the pragmatic application of research findings to actual classroom settings.  Intended for a wide ranging audience from science education faculty members and researchers to classroom teachers, school administrators, and curriculum developers, the studies reported in this book can inform best practices in K - 12 classrooms of all science disciplines and provide models of how to improve science literacy for all students.  Specific descriptions of classroom activities aimed at helping infuses the use of multimodal representations in classrooms are combined with discussion of the impact on student learning.  Overarching findings from a synthesis of the various studies are presented to help assert appropriate pedagogical and instructional implications as well as to suggest further avenues of research.